2017
DOI: 10.1090/mcom/3237
|View full text |Cite
|
Sign up to set email alerts
|

Optimal rates for Lavrentiev regularization with adjoint source conditions

Abstract: There are various ways to regularize ill-posed operator equations in Hilbert space. If the underlying operator is accretive then Lavrentiev regularization (singular perturbation) is an immediate choice. The corresponding convergence rates for the regularization error depend on the given smoothness assumptions, and for general accretive operators these may be both with respect to the operator or its adjoint. Previous analysis revealed different convergence rates, and their optimality was unclear, specifically f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…We found that there is a large amount of recent papers on conditional stability estimates in combination with variational regularization methods based more or less on reference [29]. In recent years, there have been some new works and results in this field, such as in Hilbert spaces, Hilbert scales, and Banach space settings, please see [31][32][33][34][35], etc.…”
Section: Regularization Methodsmentioning
confidence: 99%
“…We found that there is a large amount of recent papers on conditional stability estimates in combination with variational regularization methods based more or less on reference [29]. In recent years, there have been some new works and results in this field, such as in Hilbert spaces, Hilbert scales, and Banach space settings, please see [31][32][33][34][35], etc.…”
Section: Regularization Methodsmentioning
confidence: 99%
“…In fact, our regularized method can be seen as a variational method. Recently, we note that there are some new works in which the variational regularized methods are researched, such as [26][27][28][29][30], and so on. Meanwhile, this method is based on the eigenvalues and eigenfunctions of the operator involved.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(e) For recent results on adjoint source conditions for linear problems, see Plato, Hofmann, and Mathé [21]. △ (b) The rate of convergence in (4.12) is higher than those obtained by Liu and Nashed [18], Thuy [25], and Buong [8] for the penalized variational inequality method under similar source conditions.…”
Section: Convergence Rates For Regularized Solutionsmentioning
confidence: 97%